Exponential stabilization of a structural acoustic model arising in the control of noise - Diaz, Roberto; Ferreira, Marcio V.; Munoz, Jaime; Vera, Octavio; Zumelzu Carcamo, Nicolas Eduardo (My University, 2024)
We consider a coupled hybrid system whose main application is the problem of the active control of noise. The model describes the interaction of acoustic vibrations in the interior of a given two-dimensional cavity with the mechanical vibrations of two damped strings located in a part of the boundary of the cavity, in which suitable feedbacks are acting. Our main result is that the total energy associated to this model decays exponentially as time goes to infinity.
Keywords: hybrid system; exponential stability; structural acoustics; control of noise; 32w50; 37l05; 49j20